Cross-generational Physical Activity: Surveys of Children and Parents. Issue 1 (2nd January 2022) - Freire, Kate; Pope, Rod; Coyle, Julia
ABSTRACT: This study investigated the cross-generational physical activity of primary school-aged children and parents in Australia. Separate child and parent questionnaires were administered to establish a profile of the phenomenon. Cross-generational physical activity occurred across a wide variety of types of physical activity, including recreation, sport, and exercise. The study provides insight into the complexity of the physical activity partnership by showing that in a substantial proportion of partnerships, children initiate the physical activity. The importance of investigating both populations was shown as both common experiences in cross-generational physical activity, such as bonding and enjoyment were identified in addition to unique aspects. For example, child respondents disliked power, fitness, and skills mismatches whilst parent respondents disliked their children fighting and complaining. 59% of parents ranked holidays as a time they were more likely to engage in cross-generational physical activity. Findings from the surveys suggest that this physical activity partnership involves more than the provision of parental support for physical activity and modeling of a healthy behavior from parent to child.